Water availability, infrastructure and ecosystems - Smakhtin, Vladimir U.; Perera, D.; Qadir, M.; Aureli, A.; Carvalho-Resende, T.; Dhot, N.; Findikakis, A.; Villholth, Karen G.; Gurdak, J.J.; Zandaryaa, S.; Hulsmann, S.; Medlicott, K.; et al. (2020)
This chapter establishes linkages between climate change and various aspects of water management. Adaptation and resilience-building options are presented with respect to water storage – including groundwater – and water supply and sanitation infrastructure, and unconventional water supply options are described. Mitigation options for water management systems are also presented.